Not only Adventurous but also Leisure: Re-defining Tourism in Tanzanian Mount Kilimanjaro National Park - Kilungu, Halima (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
The highest mountainous tourism destinations in the world receive few numbers of tourists both domestic and international. Mount Kilimanjaro, the highest mountain in Africa is not exceptional. This is because mountains are famous as adventure destinations due to the associated risks during trekking the summit. Consequently, only risk-taker tourists trek mountains. The objective of this study is to profile attractions in Mount Kilimanjaro’s altitudinal gradients to attract adventurous, acrophobic (fear of heights), and leisure tourists using a mixed-method approach. The results revealed that each altitudinal gradient harbours unique attractions. At an altitude of 1800 -2800masl, leisure, and acrophobic tourists experience endemic forest flowers like ‘touch-me-not’ or impatiens‘and viola, and diverse wildlife species. Between 2800 and 4000 masl, floristic tourists enjoy giant groundsels, such as senecio and lobelia and the Shiraplateau. At 4000 -5000masl, where semi-adventurous hope to experience nothing, the study found attractive rocks with unique shapes like a cathedral, turtle, mushrooms, and captivating striped Zebra-like rocks. Finally, above 5000masl, the adventurer tourists experience dazzling stars at night, the snow in the tropics, and the summit. The study concludes that the diversification of attractions is likely to draw a variety of tourists, thus, boosting the overall number of tourists. Therefore, in order to increase revenue generated from tourism, tourism planners should market mountains as not only adventurous but also leisure destinations.